Paving the way for research in recruitment and selection: recent developments, challenges and future opportunities. Issue 2 (4th March 2021) - Potočnik, Kristina; Anderson, Neil R.; Born, Marise; Kleinmann, Martin; Nikolaou, Ioannis
ABSTRACT: Considered as one of the cornerstones of work and organizational psychology, it is not surprising that the selection and recruitment literature is vast. In this review, we synthesize and integrate the findings from around 40 meta-analyses and literature reviews from the last decade to identify the most recent meta-trends and future research directions in the selection and recruitment research and practice. We organize our key findings around three superordinate areas: a) recent developments in selection research, covering findings on validities of selection methods, expanding the criterion space, and applicant reactions and impression management; b) recent developments in recruitment research, paying attention to the evidence around recruitment methods and applicant attraction; and c) new technology in recruitment and selection. In our call for future research, we delineate a number of substantive issues and the need for more sophisticated theoretical developments in the field as well as methodological challenges that future efforts should address. We concur with the vast literature in that selection and recruitment research is a vibrant field, which we expect will address a number of ongoing political, cultural, technological, societal, and employment regulations-related issues to keep creating impact and providing meaningful findings for recruitment and selection practices in organizations.